The importance of bone sample selection when using radiocarbon analysis in cases of unidentified human remains. (December 2022) - Johnstone-Belford, E.; Fallon, S.J.; Dipnall, J.F.; Blau, S.
Abstract: The radiocarbon ( 14 C) analysis of skeletonised human remains can provide vital information regarding the time since death. This study analysed the 14 C content in both cortical and trabecular bone from the femur and rib of 18 human remains donated to the Australian Facility for Taphonomic Experimental Research. To determine the most appropriate bone to sample for 14 C analysis when estimating the time since death, differences in turnover time between the bone types, and the difference between environmental 14 C during the year of death (YOD) and the level of 14 C found within the bone (i.e., the lag time) were examined. Overall, the average lag time for all donors was 25 years, with the cortical bone from femur samples providing the largest lag time (39 years) and the trabecular bone from rib samples containing the lowest level of 14 C (most modern), with an average lag time of 13 years. The results of this study suggest that in cases of unidentified human remains, the analysis of trabecular bone from a rib may be preferred sample, as this bone contains the most recent 14 C, and can provide an estimate of both the time since death, and a broad approximation of YOD. Highlights: Radiocarbon content in human skeletal remains can assist in estimating time since death. Trabecular bone from rib samples contained the lowest level of 14 C. Cortical bone from femur samples contained the highest level of 14 C. The 14 C analysis of ribs may provide more precise information in forensic casework.